The Dynamics of Tourism Development: Study Case Tourism Attributes in Penyengat Island - Hary Jocom; Dodi Setiawan; Indah Andesta; Aprilyana Kusuma Dewi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
Penyengat Island has a valuable historical footprint not only for Indonesia but also for Malaysia and Singapore, as well as having a wealth of ancient literacy and influential religious values. Data were collected from tourists visiting Penyengat Island through distributing questionnaires to 100 respondents, combined with in-depth interviews, focused discussions with representative and competent key persons related to the issues discussed. This study found that the accommodation and amenities components are still the main problems in developing tourism on Penyengat Island. The factors of tourism management, tourist safety, public awareness of tourism, and environmental preservation are other central issues that need attention. The development of broad tourism promotion using information technology media and supported by professional management will be able to accelerate the tourism growth of Penyengat Island. Purpose of this study is to measure the dynamics of historical and religious tourism on Penyengat Island using the 5 A attribute approach (attractions, accessibility, accommodation, amenities and awareness). This research is focused on the empirical conditions of the dynamics of tourism development in Penyengat Island, with a qualitative descriptive research method through questionnaires, in-depth interviews, observations, and transects. The attributes of accommodation, amenities, and awareness of public tourism are still low. The main factor of the problem lies in the management of tourism in Penyengat Island that has not been done professionally and integratedly by targeting foreign tourists Overall and integrated tourism management by building destinations that ensure the comfort and safety of tourists, building information technology-based promotional media that can reach the wider community, and building a network of partnerships with stakeholders in the development of tourist destinations and strengthening human resources.